Synthesis, antimicrobial evaluation and in silico studies of the (E)-3-(aryl)-5-styryl-1,2,4-oxadiazoles (Bioscience Journal, 2022)
In recent years, investigations in the field of oxadiazoles have been intensified due to their numerous therapeutic uses. Oxadiazoles are a class of compounds that exhibit several biological applications, citing antimicrobial, anti-inflammatory, anti-diabetic, anthelmintic, anti-tumor, among others. Encouraged by the biological potential of oxadiazoles, were carried out synthesis, antimicrobial evaluation and in silica studies of five (E)-3-(aryl)-5-styryl-1,2,4-oxadiazoles. In this way, (Z)-aryl-N'-hydroxybenzimidamides and ethyl (E)-cinnamate were synthesized, which were subjected to an O-acylamidoxime reaction after by dehydration using microwave irradiation to form the oxadiazole nucleus. The compounds were characterized by spectroscopic techniques, while in vitro antimicrobial activity was evaluated against S. aureus, E. faecalis, E. coli, P. aeruginosa, and against the fungus C. utilis using the microplate microdilution method. Thus, (Z)-aryl-N'-hydroxybenzimidamides, ethyl (E)-cinnamate, and (E)-3-(aryl)-5-styryl-1,2,4-oxadiazoles were synthesized with yields ranging from moderate to good. The (E)-3-(aryl)-5-styryl-1,2,4-oxadiazoles exhibited a reduced spectrum of action, which were active against the bacterium P. aeruginosa and for the fungus C. utilis.